A proposal for zero emission from palm oil industry incorporating the production of polyhydroxyalkanoates from palm oil mill effluent - Hassan, Mohd. Ali; Nawata, Osamu; Shirai, Yoshihito; Abdul Rahman, Nor Aini; Yee, Phang Lai; Ariff, Arbakariya; Abdul Karim, Mohamed Ismail (Taylor and Francis Group, 2002)
In our previous reports, we have described the production of organic acids from palm oil mill effluent (POME) which were used as fermentation substrates to produce polyhydroxyalkanoates (PHA). Here we propose a zero emission from palm oil industry incorporating the production of PHA from POME. Our results showed that by evaporation, the organic acids could be concentrated to about 100 g·I -1 for use as substrates for the fed-batch PHA fermentation. Upon condensation of the steam, the water had a COD of 80 ppm, low enough for it to be either recycled or discharged. It was confirmed that the energy for the evaporation can be provided by combusting solid wastes such as shells and empty oil palm bunches. The concentrated organic acids were successfully converted to PHA by Ralstonia eutropha strain ATCC 17699 under a non-sterile fermentation system when the initial cell density was kept high at 4 g·I -1. After 150 hours, 20 g·I -1 cells were obtained with more than 50% PHA content. A repeated fed-batch system was also performed to obtain a high cell inoculum and to mimic the operation of a large PHA production fermentor at C/N ratios of 15 and 30 respectively, with only acetic and propionic acids as carbon sources. It was suggested that the energy for this proposed process could be sufficiently supplied by combustion of the solid wastes from the palm oil mill.